Why and How the Value of Science-Based Firms Violates Financial Theory: Implications for Policy and Governance - Sergey Bredikhin; Jonathan Linton; Thais Matoszko (Foresight and STI Governance, 2017)
How and why the positive net effect of science related activities substantially increases the value that would be anticipated by the financial theory that seems to work so well for other fields is considered here. A qualitative analysis of 25 small listed biotechnology R&D firms illustrates that these firms do not follow the neo-classical expectation of Gaussian returns. To better understand this deviation from the expected Gaussian returns the firms are compared to S&P 100 and Thomson Reuters Global Innovator List. It is found that while these large firms have a higher than expected frequency of non-Gaussian events, the causes appear to be dominated by macro-economic or industrial events that impact large numbers of firms. With the small R&D intensive biotechnology firms, it is possible to identify specific events that appear to trigger the sudden increase or decrease in value. A better understanding of the nature and magnitude of these events allows for policy makers, investors and managers to better comprehend the unusually large risks and new opportunities associated with biotechnology R&D. From this, a greater insight is afforded into the dynamic value of R&D in general.